Penerapan Water Level Control Tipe Radar dan Omron 61F-G-AP Untuk Proses Pengisian Air Bersih di Komplek Perintis Kota Banjarbaru - Lauhil Mahfudz Hayusman; Muhammad Ali Watoni; Edy Robinson; Rully Rezki Saputra (Badan Penerbitan Universitas Widyagama Malang, 2020)
Social service activities have been conducted in the Complex of Perintis of Sungai Ulin sub-district, North Banjarbaru District, Banjarbaru. The purpose of this activity is to install automation tools in the form of water level control (WLC) Radar ST 70 AB type for several reservoirs owned by residents and WLC (Omron 61F-G-AP type) in the Musalla of Perintis complex. It was done based on the team's observations in the field that there were still many reservoirs owned by residents that were not equipped with the automation equipment. In addition, many residents complained about the ineffective and inefficient process of pumping or filling water into the reservoir due to controlling and monitoring manually. As a result, many water pumps owned by the residents remain running or left running even though the water in the reservoir is fully filled. This is very detrimental to the residents, it is not only dissipation of water, but also dissipation of electric power which results in electricity bills that have to be paid every month by residents. The target of this service activity is to install the WLC equipment in several reservoirs owned by residents and reservoirs owned by Musalla in the Complex of Perintis. In addition, residents have additional skills to install WLC so that the residents can do it independently in the future Keywords: Water level control, WLC, Automation, Water reservoir